Digital Transformation of Land Title Certificates - Azizah Alvisahrin Putri Kadi; Arief Budiono; Sugeng Wibowo (Proceeding International Conference Restructuring and Transforming Law, 2024)
This paper discusses the implementation of digital transformation to land certificate issuance in Sragen Regency, focusing on efficiency, transparency, and cultural inclusion. The transition from physical to digital certificates has become a global trend, driven by advances in information technology. The research methodology involved a comprehensive literature review, analysis of existing regulations, and interviews with stakeholders to understand the current landscape and challenges around land certificate digitization in Sragen Regency. In contrast to previous research, this study specifically examines the implications of digital transformation on land certificate issuance in Sragen Regency, taking into account the unique cultural context and challenges faced by the local community. By focusing on efficiency, transparency, and cultural inclusion, this paper contributes new insights to the ongoing discourse of digitization in the field of land administration. The findings highlight the significant impact of digital transformation on administrative efficiency, information transparency, and access to land ownership data in Sragen Regency. While there is widespread support for the modernization of the land administration system, challenges related to the regulatory framework, cultural perceptions, and digital literacy need to be addressed to ensure the successful implementation of digital land certificates. The digital transformation of land certificates in Sragen Regency provides many benefits in terms of efficiency and transparency. However, to fully realize these benefits, it is important to address regulatory challenges, encourage digital literacy, and integrate local cultural values into the implementation process.